The Sound of Translation: Godot in a Translator's Anatomy - Fylaktaki, Panagiota (Σύγκριση/Comparaison/Comparison, 2020)
An overview of one of the most translated Anglosaxon plays into Greek from a socio-political and cultural perspective and the way translation is a two-way reflection of the linguistic and social milieu of every era